2023
DOI: 10.1038/s41467-023-38246-6
|View full text |Cite
|
Sign up to set email alerts
|

Integrated quantum optical phase sensor in thin film lithium niobate

Abstract: The quantum noise of light, attributed to the random arrival time of photons from a coherent light source, fundamentally limits optical phase sensors. An engineered source of squeezed states suppresses this noise and allows phase detection sensitivity beyond the quantum noise limit (QNL). We need ways to use quantum light within deployable quantum sensors. Here we present a photonic integrated circuit in thin-film lithium niobate that meets these requirements. We use the second-order nonlinearity to produce a … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 49 publications
0
10
0
Order By: Relevance
“…As a representative nonlinear optical phenomenon, second harmonic generation (SHG) effect exhibits the frequency doubling of the incident light wave, which is essential for nonlinear photonic and optoelectronic applications, such as optical switching, [1] light modulators, [2][3][4] and optical quantum information processing. [5][6][7] Traditional bulk materials with broken inversion symmetry, e.g., GaAs, [8,9] LiNbO 3 , [10,11] exhibit large second-order susceptibility. However, they suffer from irreducible volume, strict phase-matching conditions and lattice-match requirements, which limits their application in device integration.…”
Section: Introductionmentioning
confidence: 99%
“…As a representative nonlinear optical phenomenon, second harmonic generation (SHG) effect exhibits the frequency doubling of the incident light wave, which is essential for nonlinear photonic and optoelectronic applications, such as optical switching, [1] light modulators, [2][3][4] and optical quantum information processing. [5][6][7] Traditional bulk materials with broken inversion symmetry, e.g., GaAs, [8,9] LiNbO 3 , [10,11] exhibit large second-order susceptibility. However, they suffer from irreducible volume, strict phase-matching conditions and lattice-match requirements, which limits their application in device integration.…”
Section: Introductionmentioning
confidence: 99%
“…This discovery opens up new opportunities for quantum optical sensing. 33 In recent years, there has been significant progress in the manufacturing processes of photonic crystal sensors based on LiNbO 3 thin films. Tatiana et al reported the fabrication of LiNbO 3 thin films using block-shaped liquid nitrogen, followed by the production of one-dimensional photonic crystal (1D-PhC) beneath the LiNbO 3 thin film using commercial thin-film liquid nitrogen.…”
Section: Introductionmentioning
confidence: 99%
“…With an optical power of 26.2 mW, they measured a compression of (2.7±0.2)% and found that it could enhance the signal-to-noise ratio of phase measurements. This discovery opens up new opportunities for quantum optical sensing 33 . In recent years, there has been significant progress in the manufacturing processes of photonic crystal sensors based on LiNbO3 thin films.…”
Section: Introductionmentioning
confidence: 99%
“…Nonlinear optical (NLO) devices, which function on the basis of photon–photon (p-p) interactions within nonabsorbing media, play a vital role in stimulating advanced applications in modern on-chip photonic integrated circuits (PICs). Second harmonic generation (SHG), a typical nonlinear parametric process describing the frequency doubling of incident light, lies at the core of various nonlinear photonic hardware, such as optical switches, , optical modulators, , and optical quantum information processors. , Typically, for a material with a specific lattice structure, the excitation amplitude of SHG is proportional to the nonvanishing components in the second-order susceptibility tensor, which is strictly constrained by the point group symmetry that the material belongs to . Bulk crystals with noncentrosymmetric lattice structures, for example, β barium borate (β-Ba­(BO 2 ) 2 ) and lithium niobate (LiNbO 3 ), have long been a central focus in developing SHG-related devices. , However, due to the inherently weak p-p interaction in these 3D classical media, achieving appreciable SHG response remains challenging within miniaturized interaction volumes under moderate light pumping, even though the strict phase-matching conditions are satisfied. , This inevitably hinders their integration in the state-of-the-art complementary metal-oxide-semiconductor (CMOS) compatible platform, which features continuous down-scaling with high power-efficiency. , …”
mentioning
confidence: 99%
“…1−3 Second harmonic generation (SHG), a typical nonlinear parametric process describing the frequency doubling of incident light, lies at the core of various nonlinear photonic hardware, such as optical switches, 4,5 optical modulators, 6,7 and optical quantum information processors. 8,9 Typically, for a material with a specific lattice structure, the excitation amplitude of SHG is proportional to the nonvanishing components in the second-order susceptibility tensor, which is strictly constrained by the point group symmetry that the material belongs to. 10 Bulk crystals with noncentrosymmetric lattice structures, for example, β barium borate (β-Ba(BO 2 ) 2 ) and lithium niobate (LiNbO 3 ), have long been a central focus in developing SHG-related devices.…”
mentioning
confidence: 99%